Pelatihan Komunikasi Efektif dalam meningkatkan Pelayanan Prima di Instansi Pemerintahan Provinsi Jawa Barat - Maulana Rezi Ramadhana; Ratih Hasanah Sudrajat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Ineffective communication will affect the quality of a service, because it is related to the speed and accuracy of information that affects public trust. This issue is a focus on the customer service units of service agencies in the West Java provincial government, so it is necessary to increase the capacity of communication directed at excellent service. Community service activities through this form of effective communication training involve twenty-one employees of the customer service unit. Analyze training effectiveness by using score measurements before and after treatment, and needs response surveys are used to assess the usefulness of the training. The results of the training carried out showed a significant increase in scores between before and after the effective communication training, and the training received a positive response. Associated with the results of the training achieved is expected to have an impact on improving the quality of excellent service.